2009
DOI: 10.1029/2007wr006536
|View full text |Cite
|
Sign up to set email alerts
|

An agent‐based model for domestic water management in Valladolid metropolitan area

Abstract: [1] In this work we demonstrate that the combination of agent-based modeling and simulation constitutes a useful methodological approach to dealing with the complexity derived from multiple factors with influence in the domestic water management in emergent metropolitan areas. In particular, we adapt and integrate different social submodels, models of urban dynamics, water consumption, and technological and opinion diffusion, in an agent-based model that is, in turn, linked with a geographic information syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(59 citation statements)
references
References 71 publications
0
51
0
8
Order By: Relevance
“…Ref. [50] demonstrated that the ABM is a useful methodological approach to dealing with the complexity derived from multiple factors with influence in the domestic water management in emergent metropolitan areas. Ref.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…Ref. [50] demonstrated that the ABM is a useful methodological approach to dealing with the complexity derived from multiple factors with influence in the domestic water management in emergent metropolitan areas. Ref.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…Detailed, citywide ABM representation also holds promise as an integrator of multiple modeling approaches. Galán et al (2009) model technologies for household water conservation, showing that urban population dynamics and other sociogeographic effects influence technology spread in a way that may not be apparent in aggregate modeling. Such efforts highlight the different motivations, different decision frames, and different timescales relevant to water providers, sewerage providers, and water consumers, and how each can affect decisions in a dynamic context.…”
Section: Innovation In Contextmentioning
confidence: 99%
“…For instance, the IMAGES project (Deffuant et al 2002) explores opinion dynamics from a data-driven approach, using both quantitative and qualitative data; or Galán's water demand model (Galán et al 2009b), that makes an intensive use of data, specially coming from databases and survey data.…”
mentioning
confidence: 99%